Neuromuscular Activity during Cycling Performance in Hot/Dry and Hot/Humid Conditions - Michelle Baillot (MDPI AG, 2021)
To determine the relationships between limiting factors and neuromuscular activity during a self-paced 20-km cycling time trial and evaluate the effect of environmental conditions on fatigue indices. Methods: Ten endurance-trained and heat-acclimated athletes performed in three conditions (ambient temperature, relative humidity): HUMID (30 °C, 90%), DRY (35 °C, 46%) and NEUTRAL (22 °C, 55%). Voluntary muscular contractions and electromagnetic stimulations were recorded before and after the time trials to assess fatigue. The data on performance, temperature, heat storage, electromyogram, heart rate and rating of perceived exertion data were analyzed. Results: Performance was impaired in DRY and HUMID compared with NEUTRAL environment (p < 0.05). The force developed by the vastus lateral muscle during stimulation of the femoral nerve remained unchanged across conditions. The percentage of integrated electromyogram activity, normalized by the value attained during the pre-trial maximal voluntary contraction, decreased significantly throughout the trial only in HUMID condition (p < 0.01). Neuromuscular activity in peripheral skeletal muscle started to fall from the 11th km in HUMID and the 15th km in DRY condition, although core temperature did not reach critical values. Conclusions: These alterations suggest that afferences from core/skin temperature regulate the central neural motor drive, reducing the active muscle recruited during prolonged exercise in the heat in order to prevent the system from hyperthermia.